A aplicabilidade da justiça restaurativa nos casos de violência doméstica e familiar contra mulheres - Nascimento, Rayanny Sillvana Silva do (2021)
The current punitive retributive paradigm disregards the complexities of social relations in contemporary societies, especially in cases of domestic violence. According to the Brazilian Yearbook of Public Security 2021, calls for domestic violence to the Military Police indicate that every minute of 2020, 1.3 calls were requested for help due to an episode of domestic violence. The dissatisfaction of victims and the expansion of criminalization started the movement in search of alternatives, and that is how restorative justice emerged as a new paradigm that emphasizes the social and personal aspects of crime, in addition to rescuing the victim's protagonism. In the context of implementing a new conflict resolution model, the issue is the possibility of a dialogue or not between the application of restorative justice in cases of domestic and family violence. This research is justified since restorative justice is already applied in cases of domestic and family violence in some courts in Brazil and, therefore, it is important to investigate its potential and risks. The preference for research in cases of domestic violence is justified by the understanding that these conflicts differ from crimes common to urban criminality, due to their complexities and subjectivities, therefore, the victim needs a favorable space for reflection and dialogue. The main objective of this research is to analyze the applicability or not of restorative practices in domestic conflicts, since they are marked by multiple forms of violence against women and many specificities. Therefore, the methodology adopted will be a literature review in view of the need to contextualize the categories of domestic and family violence, gender and restorative justice, based on doctrine, national and international legislation, notably, taking into account Brazil and European countries. The quantitative-descriptive documentary research will enable the observation, collection and analysis of statistical data provided, predominantly, by the CNJ, FBSP, and by the data collected in the Violent Crime research group and guidelines for a public security policy in RN. As for the method of scientific approach, the hypothetical-deductive method proposed by Popper will be adopted, since the axis of the procedure will seek to prove or not the possibility of applying restorative justice in domestic conflicts. The nature of this research is applied, as it seeks to guide and support restorative practices in cases of domestic violence that develop in Brazil. It is observed that restorative justice applied to cases of domestic violence fosters a space for dialogue, empowerment and protagonism for women, reducing the chances of being victims of new domestic violence. It is also verified that restorative justice is a viable means capable of providing solutions beyond the traditional punishment, providing victims of domestic and family violence crimes a new space with sensitive treatment to the social and personal aspects of crime.